2019
DOI: 10.3889/oamjms.2019.201
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Paclitaxel, Ifosfamide, and Cisplatin (TIP) Regimen on Penile Cancer in Adam Malik Medan: A Single Center 2 Years of Experience

Abstract: BACKGROUND: Penile tumour is a rare tumour in the genitourinary system, account for 0.4-0.6%. Although rare, patients are often unaware and come in late stage, so the use of chemotherapy agents is becoming crucial. AIM: This study was conducted to evaluate responses and overall survival rate of Paclitaxel, Ifosfamide, and Cisplatin (TIP) regimen in penile cancer with nodal involvement. METHODS: We included all medical records of penile squamous cell carcinoma patients associated with nodal involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
(32 reference statements)
0
2
0
1
Order By: Relevance
“…Furthermore, the ORR and pCR rate were comparable in several studies that used TP for NAC. 16 23 25 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the ORR and pCR rate were comparable in several studies that used TP for NAC. 16 23 25 28 …”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies have currently reported the application of NAC for locally advanced penile cancers. 13 15 16 17 18 21 22 23 24 25 26 27 28 29 The efficacy and safety of NAC were assessed to achieve the most up-to-date evidence and explore the optimal chemotherapy regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Bei relativ hoher Toxizität erhielten nur 10/17 die geplanten 4 Zyklen. Es gab partielles Ansprechen in 6/17 Fällen, das Gesamtüberleben lag bei nur 6 Monaten [28]. Das TIP-Regime wurde trotzdem aufgrund der Empfehlung des NCCN der Standard in den USA [29].…”
Section: Kombinationstherapien Mit Zwei Substanzenunclassified